Removal of lead from solution by the non-viable biomass of the water fern Azolla filiculoides - Sanyahumbi, Douglas (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1999)
The removal of lead from aqueous solution and lead-acid battery manufacturing waste-water by the non-viable biomass of the water fern Azolla filiculoides was investigated in both batch and column reactors. The maximum lead uptake by the Azolla biomass at a pH value of approximately 5, was found to be 100 mg lead/g biomass from aqueous solution. Lead removal varied from 30% of the initial lead concentration at pH 1.5 to approximately 95% at pH values of 3.5 and 5.6. Lead removal from aqueous solution decreased to 30% of the initial lead concentration if the lead concentration was initially over 400 mg/l. At initial lead concentrations of less than 400 mg/l, percentage lead removal was found to be over 90% of the initial lead concentration. Lead removal remained at approximately 90% between 10°C and 50°C. Biomass concentration (4-8 mg/l) had little effect on lead removal. The presence of iron (Fe) and lead, copper (Cu) and lead or all three metal ions in solution at varying ratios to each other did not appear to have any significant effect on lead removal. Percentage lead, copper and iron removal from aqueous solution was 80-95, 45-50 and 65-75% respectively for the different multiple-metal solutions studied. No break-through points were observed for lead removal from aqueous solutions in column reactors, with initial lead concentrations of less than 100 mg/l at varying flow rates of 2, 5 and 10 ml/min. This suggested that flow rate, and therefore retention time, had little effect on percentage lead removal from aqueous solution, which was more that 95%, at low initial lead concentrations (less than 100 mg/l). At initial lead concentrations of 200 mg/l or more, an increase in flow rate, which equates to a decrease in column retention time, resulted in break-through points occurring earlier in the column run. Percentage lead removal values, from lead-acid battery efiluent in column systems, of over 95% were achieved. Desorption of approximately 30% and 40% of bound lead was achieved, with 0.5 M HNO₃ in a volume of 50 ml, from two lead-acid battery. Repeated adsorption and desorption of lead by the Azalia biomass over 10 cycles did not result in any decrease in the percentage lead removal from effluent, which strongly suggested that the Azalla biomass could be re-used a number of times without deterioration in its physical integrity, or lead removal capacity. No evidence of deterioration in the Azolla biomass's physical integrity after 10 successive adsorption and desorption procedures was observed using scanning electron microscopy. The Azolla filiculoides biomass was, therefore, found to be able to effectively remove lead from aqueous solution and lead-acid battery effluent repeatedly, with no observed reduction in it's uptake capacity or physical integrity.
Keywords: Azolla; Heavy metals -- Absorption and adsorption; Lead; Water -- Purification -- Biological treatment